The effect of hotel tax and restaurant tax contributions on local original revenue in Tolitoli regency from 2016 to 2020 - Mardiana; Ilham Rahim; Masri Arfandi; Burhanuddin; Yahya (Junal Ilmu Manajemen, 2023)
The central government's policy on regional finance aims to improve the ability of local governments to finance government affairs and development. The main source of funds is the Regional Own Revenue (PAD) and taxes and local levies are sources of revenue that can be developed. Local governments must be aware of the potential for taxes and levies and use the proper collection systems and procedures. Hotel and restaurant taxes play an important role in Regional Own Revenue and are used to finance government expenditures such as administration, infrastructure, education and health facilities, and local government activities. This phenomenon shows that local taxes are crucial in financing regional development.